Experimental Studies on Post-Explosion Lesions in a Model of Human Soft Tissues - Anna SMĘDRA; Adrian SIADKOWSKI; Jarosław BERENT (Problemy Mechatroniki)
Descriptions of blast-related injuries have long been established in the textbooks. Since, for obvious reasons, it is difficult to perform ballistic studies on human tissues, such research is usually conducted on appropriate models, i.e., gelatin blocks and soap blocks each of these materials has distinctive properties, which make them suitable for unique applications. The work aims to present the possibilities for analyzing the effects of explosion on the human body using a ballistic soap model. The tests performed allow to conclude that a shock wave affects the surface of the ballistic soap block, generating hemispherical craters, which begin to overlap when the distance between the explosive charge and block is reduced, until they form one semi-cylindrical hollow (when linear charge is used), which represents a temporary cavity. The results obtained allow for an assessment of the extent of post-explosion lesions.